Virtual and augmented reality enhanced by touch - Tao, Xiao-ming (Nature (London), 2019)
Conventional technologies for virtual and augmented reality simulate interactive experiences through visual and auditory stimuli. A technology that adds sensations of touch could find uses in areas from gaming to prosthetic feedback. Skin-integrated wireless touch-based interfaces.